Sugarcane Bagasse Ash Micronized Using Air Jet Mills for Green Pozzolan in Brazil - Rafael G. D. Molin Filho; Jaciele M. Rosso; Eduardo A. Volnistem; Romel D. Vanderlei; Leda M. S. Colpini; Mateus M. Ferrer; Paulo R. Paraíso; Luiz M. de M. Jorge (International Journal of Chemical Engineering)
This study provided a basis for new possibilities concerning the use of the sugarcane bagasse ash as a green pozzolanic addition to the Portland cement composite. To that effect, a simple micronization method using air jet milling without any other additional thermal procedure was used to control the characteristics of ash particles. This procedure not only maintains the required characteristics of the residues but can also improve some of them. Sugarcane bagasse ash is a residue produced on large scale in Brazil by ethanol and sugar plants as a result of the burning of sugarcane bagasse in energy cogeneration. The residue used in this study was initially characterized by scanning electron microscopy, granulometric and specific mass analyses, N2 adsorption measurements, X-ray diffraction, X-ray fluorescence spectroscopy, and thermogravimetric analysis with differential thermal analysis. Pozzolanic ash activity was evaluated according to the axial compressive strength at 28 days and the modified Chapelle methods. The results showed that the milling fly sugarcane bagasse ash samples presented satisfactory pozzolanic activity.